Prognostic Value of Neutrophil to Lymphocyte Ratio on Pathologic Findings of Transrectal Ultrasonography Guided Biopsy of Prostate - Iraj Khosrovpanah; Sadeq Rostami; Zhoobin Heidari bateni; Mojtaba Teimoori; Darya Khosrovpanah (Iranian Society of Pathology, 2018)
Background and Objective: Prostate cancer is considered as one of the most common malignancies in males. Despite the decreasing trend during the past decade, the incidence continues to rise in adolescents worldwide. Recently, new emerging technologies beside TRUS-guided prostate biopsy were introduced and showed high potential in the diagnosis of prostate cancer. The current study aimed at investigating the role of blood cell count and its prognostic value on pathologic findings.Methods:The current prospective analysis was conducted on patients with abnormality from January 2013 to January 2015. A total of 168 CBC tests including absolute Neutrophil and lymphocyte counts were performed on males at the Department of Urology, Razi University Hospital (Guilan, Iran). Of these, all males had both CBCs and free:total (F/T) prostate-specific antigen (PSA) ratio.Results: Average age of patients was 63.5±7. It was observed that Neutrophil count and Neutrophil percentage was not significantly different among the groups with different pathologies. In comparison to biopsy findings none of the cell count had suitable specificity and sensitivity. In the multivariate analysis to predict malignancy, only age (B=0.1, S.E=0.04, EXP [B]) =1.1 and sig=0.00) and PSA level (B=0.1, S.E=0.04, EXP [B]) =1.1 and sig=0.00) were significant.Conclusions: In comparison to biopsy findings, none of the cell counts (absolute or percent) had suitable specificity and sensitivity, and the cell count and percentage before biopsy were not different among the groups with different pathologies. Powerful and long-term studies are required to evaluate prognostic values of cell count on adenocarcinoma.